Nanoporous layer formation on the Ti10Mo8Nb alloy surface using anodic oxidation - Carobolante, João Pedro Aquiles [UNESP]; da Silva, Kerolene Barboza [UNESP]; Chaves, Javier Andres Munoz; Dias Netipanyj, Marcela Ferreira; Popat, Ketul Chandrakant; Alves Claro, Ana Paula Rosifini [UNESP] (Elsevier, 2020)
Beta titanium alloys with a low elastic modulus, such as Ti10Mo8Nb alloy, are suitable to relieve the stress shielding effect that occurs in the interface implant/bone. However, these materials are considered bioinert and changing the surface topography is necessary to improve cell adhesion and, consequently, osseointegration. The purpose of this research is the surface modification of Ti10Mo8Nb experimental alloy using anodic oxidation. Ingots of Ti10Mo8Nb experimental alloy were produced by melting in arc melting furnace, cold worked and heat treatment. The anodic oxidation was performed to change the alloy surface using an organic electrolyte under 20 V for 10.8 ks at room temperature. The Ti10Mo8Nb alloy exhibited a beta phase and after the surface treatment, a hydrophilic nanoporous layer of TiO2 was obtained. The anatase phase was observed in the annealed samples around 400 °C without deterioration of this nanostructure. Under these conditions, the sample there was a tendency to improve cellular behavior on the material surface due to their hydrophilic behavior as compared to the sample without surface treatment and the nanoporous layer in the amorphous state. In this sense, the adequate bulk properties together suitable surface response makes Ti10Mo8Nb alloy attractive for biomedical applications.
Keywords: Anodic oxidation; Nanoporous; Surface modification; Titanium alloys